Pronounced Structural and Functional Damage in Early Adult Pediatric-Onset Multiple Sclerosis with No or Minimal Clinical Disability - Giorgio, Antonio; Zhang, Jian; Stromillo, Maria Laura; Rossi, Francesca; Battaglini, Marco; Nichelli, Lucia; Mortilla, Marzia; Portaccio, Emilio; Hakiki, Bahia; Amato, Maria Pia; De Stefano, Nicola (Frontiers in Neurology, 2017)
Pediatric-onset multiple sclerosis (POMS) may represent a model of vulnerability to damage occurring during a period of active maturation of the human brain. Whereas adaptive mechanisms seem to take place in the POMS brain in the short-medium term, natural history studies have shown that these patients reach irreversible disability, despite slower progression, at a significantly younger age than adult-onset MS (AOMS) patients. We tested for the first time whether significant brain alterations already occurred in POMS patients in their early adulthood and with no or minimal disability (n=15) in comparison to age- and disability-matched AOMS patients (n=14) and to normal controls (NC, n=20). We used a multimodal MRI approach by modelling, using FSL, voxelwise measures of microstructural integrity of white matter tracts and grey matter volumes with those of intra- and internetwork functional connectivity (analysis of variance, p≤0.01, corrected for multiple comparisons across space). POMS patients showed, when compared with both NC and AOMS patients, altered measures of diffusion tensor imaging (reduced fractional anisotropy and/or increased diffusivities) and higher probability of lesion occurrence in a clinically eloquent region for physical disability such as the posterior corona radiata. In addition, POMS patients showed, compared with the other two groups, reduced long-range functional connectivity, assessed from resting functional MRI, between default mode network and secondary visual network, whose interaction subserves important cognitive functions such as spatial attention and visual learning. Overall, this pattern of structural damage and brain connectivity disruption in early adult POMS patients with no or minimal clinical disability might explain their unfavourable clinical outcome in the long term.